Constructive and investigative knowledge production in corrosion science practices (Research, Society and Development, 2016)
In engineering courses, the epistemological foundations of a science in corrosion are hardly discussed, which leads to discipline be considered difficult to understand. This encourages the search for a more attractive approach by the teacher. The aim of this study was to show how it is possible to overcome the paradigm of difficulty learning corrosion and its chemical mechanisms using an active learning methodology. We conducted a qualitative research, which proposes an investigative approach to the construction of knowledge through the practice of corrosion. It was found that the students and teacher liked the part practices and large classes said there were improved learning in relation to corrosion science practices. It was possible to overcome the paradigm of difficulty in learning and its chemical corrosion mechanisms, through an active learning methodology approach, constructive and investigative knowledge production in relation to corrosion.